Co-relation between heavy metal resistance and antibiotic susceptibility in halotolerant bacteria isolated from the antarctic oceanic region - ANURADHA R MULIK; RAMA K BHADEKAR (International Journal of Pharma and Bio Sciences, 2017)
Four bacterialisolatesvizKocuriasp BRI 36, Brevibacillussp BRI 37, Halomonassp BRI 38 andOceanobacillussp BRI39 from Antarctic oceanic region exhibitinghigh tolerance to heavy metals like cadmium, chromium, nickel and lead were selected for this study. Their maximum tolerable concentration MTC values were found to be in the range of 300 to 600 ppm. Interestingly,the isolates exhibited growth in presence of multiple metals at various temperatures (15, 30 and 45°C). The characteristicof metal resistance is known to be linked to antibiotic resistance and mostly associated with plasmid DNA. In order to determine role of plasmid DNA, curing experiments were performed using ethidium bromide andSodium dodecyl sulfate SDS. Cured BRI isolates were again examined for metal tolerance and antibiotic susceptibility pattern. MTC values for the selected four metals were almost similar to those prior to curing. However, antibiotic susceptibility experiments revealed increase in sensitivity topiperacillin and chloramphenicolincured BRI 36whereas, remaining isolates demonstrated similar response to the antibiotics tested after curing. The observations indicated possible role of plasmid in piperacillin and chloramphenicol resistance in BRI 36whereas, in other isolates it may or may not be plasmid linked. However, metal resistance characteristics of BRI isolates appear to be independent of extra chromosomal DNA, since the MTC results remained unaltered after curing.